2011
DOI: 10.17221/1305-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of missense mutation Asp298Asn in MC4R on growth and fatness traits in commercial pig crosses in the Czech Republic

Abstract: Abstract:The current knowledge of factors regulating voluntary feed intake in pigs is quite limited. The objective of this study was to test the influence of the missense mutation p.Asp298Asn (AF087937:c.746G>A) of the MC4R gene on selected production traits in pig crosses. These crosses are commonly used on commercial farms in the Czech Republic. The allele frequencies of c.746G>A were as follows: G allele -0.59 and A allele -0.41. We detected statistically significant differences in the content of intramuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…The obtained QTL for DFI and DOT located on SSC 1 pointed to the MC4R locus at 178.5 Mb which is widely discussed for contributions to the phenotypic variance of feeding behaviour traits and feed intake in pigs (Kim et al 2000 ). The proposed causal MC4R (Asp298Asn) mutation affects energy homeostasis influencing back fat thickness, weight gain, and feed intake but at the same time showing inconsistencies in its penetrance in different populations (Kim et al 2000 ; Piórkowska et al 2010 ; Dvořáková et al 2011 ). Moreover, the current and other studies provided evidence that the genomic region around MC4R includes other, potentially pleiotropic-acting, genetic variants influencing FE and feeding behaviour traits (Jiao et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The obtained QTL for DFI and DOT located on SSC 1 pointed to the MC4R locus at 178.5 Mb which is widely discussed for contributions to the phenotypic variance of feeding behaviour traits and feed intake in pigs (Kim et al 2000 ). The proposed causal MC4R (Asp298Asn) mutation affects energy homeostasis influencing back fat thickness, weight gain, and feed intake but at the same time showing inconsistencies in its penetrance in different populations (Kim et al 2000 ; Piórkowska et al 2010 ; Dvořáková et al 2011 ). Moreover, the current and other studies provided evidence that the genomic region around MC4R includes other, potentially pleiotropic-acting, genetic variants influencing FE and feeding behaviour traits (Jiao et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous data have shown that A allelic variant of MC4R is associated with best value of Days to 100 kg, however G allele and especially GG/MC4R genotype is associated with improved BF and meat traits (Dvořáková et al, 2011;Munoz et al, 2011;Van den Broeke et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Civáňová and Knoll (2007) reported a statistically significant association of the MC4R gene and lean meat content in the Black Pied Přeštice pigs (GA > AA, P ≤ 0.05), and Kim et al (2000) revealed the G allele association with lower backfat thickness, slower growth, and lower daily gain and lower feed intake in four different commercial lines of PIC (international pig breeding company) pigs derived from European/American breeds. Dvořáková et al (2011) found out an association between the G allele and higher values of lean meat content, muscle depth of musculus gluteus and musculus longissimus lumborum et thoracis in the population that included seven commercial crosses and one pure breed. The influence of G allele was similar in our study and in the studies of Civáňová and Knoll (2007), Kim et al (2000) and Dvořáková et al (2011) in Black Pied Přeštice, European/American PIC pigs and commercial crosses, respectively.…”
Section: And Discussionmentioning
confidence: 96%
“…Dvořáková et al (2011) found out an association between the G allele and higher values of lean meat content, muscle depth of musculus gluteus and musculus longissimus lumborum et thoracis in the population that included seven commercial crosses and one pure breed. The influence of G allele was similar in our study and in the studies of Civáňová and Knoll (2007), Kim et al (2000) and Dvořáková et al (2011) in Black Pied Přeštice, European/American PIC pigs and commercial crosses, respectively. On the other hand, the G allele was associated with the fattest animals in the line which was derived by crossing a Chinese (Meishan) breed with a line of Large White origin.…”
Section: And Discussionmentioning
confidence: 96%